INVESTIGASI MODEL MENTAL PADA MATERI ALKOHOL MENGGUNAKAN TES DIAGNOSTIK INTERVIEW ABOUT EVENT (Universitas Negeri Semarang, 2020)
As chemistry teacher candidates, chemistry education students should have a complete mental model, including alcohol. But in reality, 42% of prospective chemistry teacher students at one of the state universities found that alcohol material was difficult to understand. These difficulties are indicators of the lack of mental models of the chemistry teacher candidates. This study aims to explore the types of mental models of prospective chemistry teachers on alcohol material. This research is a type of descriptive research with a qualitative approach. The subjects of this study were students of the Department of Chemistry Education in 2016. The sample was selected using a purposive sampling technique. The number of samples determined was 12 students with different levels of understanding. Mental model excavations were performed using the Diagnostic Test Mental-Interview About Event (TDM-IAE). The diagnostic test consists of open-ended questions, drawing submicroscopic representation activities, and interviews. The results showed that in general chemistry teacher candidates had a synthetic mental model with a percentage of 66.66% verbal description answers. In the picture answers, all chemistry teacher candidates have a synthetic mental model.